Investigation the effect of linkers in Zinc Porphyrin dimer Molecular Junctions on the Electrical and Thermoelectric Properties - Preesam, Dhia Saiwan (University of Thi-Qar Journal, 2025)
The development of higher oligomeric porphyrin arrays represents a promising pathway toward next-generation molecular electronics. In this study, the thermoelectric properties of five zinc porphyrin dimers (ZnP) were theoretically investigated by analyzing electron transport through Zn-porphyrin dimers connected between gold electrodes via five distinct configurations. The impact of the presence, type, position, and number of linkers on the electrical and thermoelectric properties was systematically examined. The results demonstrate that transitioning from direct to linker-mediated contacts significantly alters both electrical and thermal conductance. Moreover, variations in linker position and number strongly influence electrical conductivity, thermal conductivity, and thermopower (S). These findings underscore the critical role of linker engineering in controlling the electrical and thermoelectric performance of zinc porphyrin dimers for molecular electronic applications.